Mobile-Based Applications: The Legal Challenges on Data Privacy - Zirawani Baharum; Faradina Ahmad; Muhammad Imran Qureshi; Nasien, Dewi; Adiya, M. Hasmil (International Journal of Online and Biomedical Engineering (iJOE), 2023)
The mobile-based apps used is getting popular and continued to increased. Mobile user often downloaded the apps from various sources that provided from numerous of categorization of the application included health apps. Some of apps is optional to choose, but nevertheless, there are several apps is compulsory or must-action by citizens as instructed by the government or their agency. As for that, some issues of legal challenges on data privacy kin to data security have occurred. The issues on legal challenges is more intricate for non-legal educated users with non-awareness citizens while there are government involvements. Hence, in this paper, the issues and the legal challenges on the data privacy for mobile-based application are reviewed to give awareness for both side, the users (citizens) and apps provider (government or developer). Together with that, the idea of action, such as recommendation and option to react with the issues and challenges are also presented. Several Acts (legislation) are also proposed according to the legal issues and challenges that occurred, as showed the Personal Data Protection Act (PDPA) 2010 is became as the famous act used to confront with the existing privacy legislation in mobile-based application. The suggestions and recommendations might assist citizens to keep stand with their rights on data privacy issues in mobile apps, and to the other-side, it might provide some idea be more precise when create and develop the mobile apps.